Cerebral atrophy in myotonic dystrophy: a voxel based morphometric study. Issue 11 (15th October 2004) - Antonini, G; Mainero, C; Romano, A; Giubilei, F; Ceschin, V; Gragnani, F; Morino, S; Fiorelli, M; Soscia, F; Di Pasquale, A; Caramia, F
Abstract : Brain involvement in myotonic dystrophy type 1 (DM1) is characterised by cortical atrophy and white matter lesions. We compared the magnetic resonance imaging derived grey matter maps of 22 DM1 patients with those of matched, healthy controls using voxel based morphometry to evaluate the extension of global and regional cortical atrophy in DM1, as well as its relationships with clinical and genetic features. Patients had significantly reduced brain tissue volumes. Grey matter volume was inversely correlated with age; this inverse correlation was significantly stronger in DM1 than in controls. Neither the clinical and genetic characteristics nor white matter lesions were correlated with cortical atrophy. Grey matter atrophy was located mainly in the bilateral frontal and parietal lobes, in the bilateral middle temporal gyrus, and in the left superior temporal and occipital gyrus.